Optimal capacitor placement and sizing using stochastic optimization for energy efficiency of a building / Amirul Asyraf Mohd Kamaruzaman …[et al.] - Mohd Kamaruzaman, Amirul Asyraf; Othman, Muhammad Murtadha; Mohd Arriffin, Aainaa; Musirin, Ismail (Universiti Teknologi MARA, 2019)
This paper presents the optimal location and sizing of capacitors to reduce the total power losses as well as its investment cost for a unbalanced electrical system of a building. The capacitors location and sizing will be randomly chosen repetitively, via Stochastic optimization method using MATLAB® and SIMULINK® software. The optimal capacitors location and sizing will be picked via analysis and comparisons between the results. The result shows improvement in power losses with minimal investment cost whilst providing optimal sizing and location of capacitors to be installed in a building.